Fast Screening for Antioxidant Properties of Flavonoids from Pterogyne nitens Using Electrochemical Methods - Okumura, Leonardo Lutz; Regasini, Luis Octavio [UNESP]; Fernandes, Daniara Cristina [UNESP]; Siqueira da Silva, Dulce Helena [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP]; Bolzani, Vanderlan da Silva [UNESP] (Aoac Int, 2012)
A fast, low-cost, convenient, and especially sensitive voltammetric screening approach for the study of the antioxidant properties of isoquercitrin and pedalitin from Pterogyne nitens is suggested in this work. These flavonoids were investigated for their redox properties using cyclic voltammetry in nonaqueous media using N,N-dimethylformamide and tetrabutylammonium tetrafluorborate as the supporting electrolyte, a glassy carbon working electrode, AglAgCl reference electrode, and Pt bare wire counter electrode. The comparative analysis of the activity of rutin has also been carried out. Moreover, combining HPLC with an electrochemical detector allowed qualitative and quantitative detection of micromolecules (e.g., isoquercitrin and pedalitin) that showed antioxidant activities. These results were then correlated to the inhibition of p-carotene bleaching determined by TLC autographic assay and to structural features of the flavonoids.